x 3 + 2 x 2 + 3 x + 1 = 0
Let p , q , r be three distinct complex numbers that satisfies the above cubic equation. Evaluate the last three digits of:
p 8 1 + q 8 1 + r 8 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
isnt there a easy solution
Log in to reply
no
Log in to reply
I've presented a slightly easier solution, though the only difference is that I use algebra to treat the general case and iterate it, whereas Pi Han chose to labour through the calculations repeatedly.
can we find - p 7 9 + q 7 9 + r 7 9 ?
Here's another potential approach, although its a lot more tedious than the approach above.
Let p n + q n + r n = S n . Substituting p, q, r into the equation and summing, we have S 3 + 2 S 2 + 3 S 1 + 3 = 0 . Using Viete's relations, we have S 0 = 3 , S 1 = − 2 , S 2 = − 2 .
Multiplying through by p n , q n , r n , and summing, we have the recursion S n + 3 + 2 S n + 2 + 3 S n + 1 + S n = 0 . Using the values above m o d 1 0 0 0 we can chase down the value of S 8 1 after a fair amount of tedious numerical work.
This solution echos what Pi Han does, but presents it in a cleaner fashion. You will see glimpses of what he does. The main difference is that I use algebra to treat the general approach, and iterate it several times, as opposed to Pi Han who performs the calculations several times.
Lemma. Suppose that α , β , γ are roots to the cubic equation x 3 + a x 2 + b x + c = 0 . Then α 3 , β 3 , γ 3 are roots to the cubic equation X 3 + ( 3 c + a 3 − 3 a b ) X 2 + ( 3 c 2 + b 3 − 3 a b c ) X + c 3 = 0 .
Proof of Lemma.
Apply Vieta's formula. Observe that
α
3
+
β
3
+
γ
3
=
(
α
+
β
+
γ
)
3
−
3
(
α
+
β
+
γ
)
(
α
β
+
β
γ
+
γ
α
)
+
3
α
β
γ
,
α
3
β
3
+
β
3
γ
3
+
γ
3
α
3
=
(
α
β
+
β
γ
+
γ
α
)
3
−
3
(
α
+
β
+
γ
)
(
α
β
+
β
γ
+
γ
α
)
(
α
β
γ
)
+
3
(
α
β
γ
)
2
,
α
3
β
3
γ
3
=
(
α
β
γ
)
3
.
Note that Pi Han essentially used these formulas too.
Corollary. We thus get that
p 3 , q 3 , r 3 are roots of x 3 − 7 x 2 + 1 2 x + 1 = 0 ,
p 9 , q 9 , r 3 are roots of x 3 − 8 8 x 2 + 1 9 8 3 x + 1 = 0 ,
p 2 7 , q 2 7 , r 2 7 are roots of x 3 − 1 5 7 9 5 7 x 2 + 7 7 9 8 2 5 2 6 0 2 + 1 = 0 ,
And finally, p 8 1 + q 8 1 + r 8 1 = ( 1 5 7 9 5 7 ) 3 − 3 × 1 5 7 9 5 7 × 7 7 9 8 2 5 2 6 0 2 + 3 × 1 .
Alternative proof of lemma. (For those who don't like the 'amazing formulas' shown above. Though, this only works well for small degrees, since it is otherwise hard to force out the amazing formulas.)
Observe that x 3 + c = − a x 2 − b x . Cubing both sides, we obtain that
x 9 + 3 x 6 c + 3 x 3 c 2 + c 3 = − a 3 x 6 − 3 a 2 b x 5 − 3 a b 2 x 4 − b 3 x 3 .
Every exponent of x is a multiple of 3, with the exception of − 3 a 2 b x 5 − 3 a b 2 x 4 . Luckily, we can express this as − 3 a b x 3 ( a x 2 + b x ) = − 3 a b x 3 ( − x 3 − c ) = 3 a b x 6 + 3 a b c x 3 .
Hence, we have
x 9 + ( 3 c + a 3 − 3 a b ) x 6 + ( 3 c 2 + b 3 − 3 a b c ) x + c 3 = 0 .
As such, the cubic equation
X 3 + ( 3 c + a 3 − 3 a b ) X 2 + ( 3 c 2 + b 3 − 3 a b c ) X + c 3 = 0 .
would have roots of the form α 3 , β 3 , γ 3 .
Oh my goddddddd! So what if it is given a 5th degree polynomial and you want to find the sum of roots raised to the powers of power of 5? Can we generalize it to any positive integer n > 1 ?
Log in to reply
Yes it does. The main difficulty is knowing how to express these (symmetric) polynomials in terms of the elementary symmetric polynomials. You can read about how any symmetric polynomial can be given by an expression involving only additions and multiplication of constants and elementary symmetric polynomials
Well, I think I'm asking a little too much. Just stating α 7 β 7 + α 7 γ 7 + β 7 γ 7 in terms of α + β + γ , α β + α γ + β γ , α β γ is already such a hassle.
Hah, I got lazy trying to state α 3 β 3 + α 3 γ 3 + β 3 γ 3 like how you did. So I chose the g n ( x ) = x 3 f n ( x 1 ) route.
The main motive of this solution is to explain the fact that, not only p 8 1 + q 8 1 + r 8 1 , but we can calculate the values of p 1 k + p 2 k + p 3 k + … + p n k for any k ≥ 1 , k ∈ N using a single two step process.
This is a solution which uses Companion Matrix Methods and a heavy computational calculation.
Let P ( x ) = x 3 + 2 x 2 + 3 x + 1 .
Let Q ( x ) be a polynomial whose roots are 8 1 s t powers of the roots of P ( x ) .
We'll use the companion matrix of the polynomial P ( x ) namely:
A = ⎝ ⎛ 0 1 0 0 0 1 − 1 − 3 − 2 ⎠ ⎞
for which the characteristic polynomial is det ( x I − A ) = x 3 + 2 x 2 + 3 x + 1 . For each integer k ≥ 1 , the zeroes of the characteristic polynomial of A k are the k t h powers of the zeroes of P ( x ) . Taking this into account, we find that Q ( x ) = det ( x I − A 8 1 ) . Using Scientific Calculators, we obtain:
A 8 1 = ⎝ ⎛ 1 4 1 0 0 6 8 3 7 9 1 0 4 0 0 2 5 5 8 6 8 9 3 5 6 8 3 9 0 1 − 1 6 7 2 2 2 0 5 9 6 1 0 3 7 5 1 6 7 2 2 2 0 5 9 6 1 0 3 7 5 6 4 2 6 7 3 0 1 6 7 4 1 5 2 5 5 9 0 3 1 3 0 5 4 9 0 4 6 5 1 − 5 9 0 3 1 3 0 5 4 9 0 4 6 5 1 − 1 6 0 3 7 1 7 1 0 5 1 0 3 5 7 8 − 5 3 7 9 5 3 0 9 3 0 6 7 7 7 7 ⎠ ⎞
Thus we have Q ( x ) as:
Q ( x ) = det ( x I − A 8 1 )
= ∣ ∣ ∣ ∣ ∣ ∣ x − 1 4 1 0 0 6 8 3 7 9 1 0 4 0 0 − 2 5 5 8 6 8 9 3 5 6 8 3 9 0 1 1 6 7 2 2 2 0 5 9 6 1 0 3 7 5 − 1 6 7 2 2 2 0 5 9 6 1 0 3 7 5 x − 6 4 2 6 7 3 0 1 6 7 4 1 5 2 5 − 5 9 0 3 1 3 0 5 4 9 0 4 6 5 1 5 9 0 3 1 3 0 5 4 9 0 4 6 5 1 1 6 0 3 7 1 7 1 0 5 1 0 3 5 7 8 x + 5 3 7 9 5 3 0 9 3 0 6 7 7 7 7 ∣ ∣ ∣ ∣ ∣ ∣
= x 3 − 2 4 5 7 2 6 7 6 1 5 8 4 1 4 8 x 2 + 4 7 4 2 3 3 1 3 6 3 6 1 2 6 2 8 1 8 1 6 7 3 5 4 3 5 3 5 5 3 x + 1
Thus, we know that if p , q , r are the roots of P ( x ) , then p 8 1 , q 8 1 , r 8 1 are the roots of Q ( x ) .
Therefore, by Vieta's Formula, the sum of roots of Q ( x ) or p 8 1 + q 8 1 + r 8 1 equals 2 4 5 7 2 6 7 6 1 5 8 4 1 4 8 and it's last three digits being 1 4 8 .
Since I had no scientific calculators to perform heavy calculations, I preferred Wolfram-Mathematica.
You should learn how to diagonalize a matrix to find the exponentiation efficiently.
Problem Loading...
Note Loading...
Set Loading...
Note that 8 1 = 3 4 .
Let f n ( x ) and g n ( x ) = x 3 f n ( x 1 ) be 3 rd degree polynomials with integer coefficient such that f n ( x ) has zeros p 3 n , q 3 n , r 3 n while g n ( x ) has zeros p − 3 n , q − 3 n , r − 3 n , where n = 0 , 1 , 2 , 3
So f 0 ( x ) = x 3 + 2 x 2 + 3 x + 1 . By Vieta's formula, p + q + r = − 2 , p q + p r + q r = 3 , p q r = − 1 . Apply the algebraic identity
p 3 + q 3 + r 3 − 3 p q r = ( p + q + r ) ( ( p + q + r ) 2 − 3 ( p q + p r + q r ) ) ⇒ p 3 + q 3 + r 3 = 7
And g 0 ( x ) = x 3 + 3 x 2 + 2 x + 1 ⇒ p 1 + q 1 + r 1 = − 3 , ⇒ p q 1 + p r 1 + q r 1 = 2
( p 1 ) 3 + ( q 1 ) 3 + ( r 1 ) 3 − p q r 3 = ( p 1 + q 1 + r 1 ) ( ( p 1 + q 1 + r 1 ) 2 − 3 ( p q 1 + p r 1 + q r 1 ) )
⇒ p 3 1 + q 3 1 + r 3 1 = − 1 2 ⇒ ( p q r ) 3 p 3 q 3 + p 3 r 3 + q 3 r 3 = − 1 2 ⇒ p 3 q 3 + p 3 r 3 + q 3 r 3 = 1 2
f 1 ( x ) = x 3 − 7 x 2 + 1 2 x + 1 ⇒ g 1 ( x ) = x 3 + 1 2 x 2 − 7 x + 1
Apply the same method above:
p 9 + q 9 + r 9 − 3 ( p q r ) 3 = ( p 3 + q 3 + r 3 ) ( ( p 3 + q 3 + r 3 ) 2 − 3 ( p 3 q 3 + p 3 r 3 + q 3 r 3 ) )
⇒ p 9 + q 9 + r 9 = 8 8
( p 3 1 ) 3 + ( q 3 1 ) 3 + ( r 3 1 ) 3 − ( p q r ) 3 3 = ( p 3 1 + q 3 1 + r 3 1 ) ( ( p 3 1 + q 3 1 + r 3 1 ) 2 − 3 ( p 3 q 3 1 + p 3 r 3 1 + q 3 r 3 1 ) )
⇒ p 9 1 + q 9 1 + r 9 1 = − 1 9 8 3 ⇒ p 9 q 9 + p 9 r 9 + q 9 r 9 = 1 9 8 3
f 2 ( x ) = x 3 − 8 8 x 2 + 1 9 8 3 x + 1 ⇒ g 2 ( x ) = x 3 + 1 9 8 3 x 2 − 8 8 x + 1
Repeat:
p 2 7 + q 2 7 + r 2 7 − 3 ( p q r ) 9 = ( p 9 + q 9 + r 9 ) ( ( p 9 + q 9 + r 9 ) 2 − 3 ( p 9 q 9 + p 9 r 9 + q 9 r 9 ) )
⇒ p 2 7 + q 2 7 + r 2 7 = 1 5 7 9 5 7
( p 9 1 ) 3 + ( q 9 1 ) 3 + ( r 9 1 ) 3 − ( p q r ) 9 3 = ( p 9 1 + q 9 1 + r 9 1 ) ( ( p 9 1 + q 9 1 + r 9 1 ) 2 − 3 ( p 9 q 9 1 + p 9 r 9 1 + q 9 r 9 1 ) )
⇒ p 2 7 1 + q 2 7 1 + r 2 7 1 = − 7 7 9 8 2 5 2 6 0 2 ⇒ p 2 7 q 2 7 + p 2 7 r 2 7 + q 2 7 r 2 7 = 7 7 9 8 2 5 2 6 0 2
f 3 ( x ) = x 3 − 1 5 7 9 5 7 x 2 + 7 7 9 8 2 5 2 6 0 2 x − 1
Repeat one last time
p 8 1 + q 8 1 + r 8 1 − 3 ( p q r ) 2 7 = ( p 2 7 + q 2 7 + r 2 7 ) ( ( p 2 7 + q 2 7 + r 2 7 ) 2 − 3 ( p 2 7 q 2 7 + p 2 7 r 2 7 + q 2 7 r 2 7 ) )
Modulo 1 0 0 0 :
p 8 1 + q 8 1 + r 8 1 ≡ ≡ ≡ ≡ 1 5 7 9 5 7 ( 1 5 7 9 5 7 2 − 3 ⋅ 7 7 9 8 2 5 2 6 0 2 ) − 3 9 5 7 ( 9 5 7 2 − 3 ⋅ 6 0 2 ) − 3 − 4 3 ( 4 3 2 − 1 8 0 6 ) − 3 1 4 8